Enhancing Wi-Fi Link-Layer Reliability for Real-Time Collaboration: A Simulation-Based Performance Evaluation - J., Vijitha Ananthi; G., Harshita; R., Gnaneswar; I., Charishma; D.S., Dhanush (IRO Journal on Sustainable Wireless Systems, 2025)
A reliable Wi-Fi network is required to enable real-time collaboration for situations like campus hackathons that participants utilize wireless connectivity for tasks like screen sharing and code synchronization. The consumers experience of missed content or duplicate updates suggests issues with the link layer rather than the physical layer, despite a variety of strong network signals. Basic processes that directly affect data consistency and integrity across different devices and operating systems are handled by the link layer including framing, error detection, flow control, acknowledgments and retransmissions. This study explains the influence of link-layer behavior on data dependability in dense heterogeneous Wi-Fi networks. It demonstrates that differences in driver implementation, retransmission policy and acknowledgment processing result in irregular content delivery. A WLAN simulation was built using Cisco Packet Tracer to simulate real-time data transport under various loads and interference conditions. The purpose of simulating the link layer services is to transmit content without duplication or corruption, the simulation examines packet retransmission, acknowledgment latency and frame loss. The results demonstrate that adjustments to retransmission limits, block ACK activation, and adaptive flow control design improve dependability. Wi-Fi 6/6E access points, QoS prioritization (IEEE 802.11e/WMM), and comparable NIC firmware versions on devices improve stability and lower latency. The study results, indicate that link-layer efficiency in wireless dependability is affected as much by signal strength as by other factors.
Keywords: Wi-Fi; Link Layer; Error Detection; Flow Control; Retransmissions; Acknowledgments; Wireless Reliability; Real-time Collaboration; WLAN.